2019
DOI: 10.29271/jcpsp.2019.08.724
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Transporter 1 Overexpression in Oral Squamous Cell Carcinoma

Abstract: Methodology: A total of 57 patients, who have been diagnosed with chronic adenotonsillitis and operated for obstruction or infection, were included in the study. Patients were divided into two groups according to their palatine tonsil sizes. Each patient performed voice analysis preoperatively and one month postoperatively, recruiting both objective and subjective methods. F0, jitter % and shimmer % values were assessed with objective methods; while subjective methods evaluated pediatric voice handicap index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
(6 reference statements)
1
6
0
1
Order By: Relevance
“…Staining intensity was reported by numerous authors, and although the vast majority of tumours fell into the "moderate" to "high" ranges, there were drastically different findings, with intense staining (IHC score ≥ 3) of GLUT-1 found to range from 0.3% to 63% in eight studies [52,54,56,63,64,72,73,76].…”
Section: Patient Samples (Protein)mentioning
confidence: 87%
See 3 more Smart Citations
“…Staining intensity was reported by numerous authors, and although the vast majority of tumours fell into the "moderate" to "high" ranges, there were drastically different findings, with intense staining (IHC score ≥ 3) of GLUT-1 found to range from 0.3% to 63% in eight studies [52,54,56,63,64,72,73,76].…”
Section: Patient Samples (Protein)mentioning
confidence: 87%
“…Estilo et al found that 30.6% of patients had high levels of GLUT-3 expressed, compared to normal tissue [81]. In contrast, Qamar found in a cohort of 60 patients that GLUT-1 was only positive in 10% of smokers but was expressed in 82.7% of non-smokers [64]. Similarly, Choi et al found that smoking status was not associated with GLUT-1 expression.…”
Section: Gluts and Clinicopathologic Characteristicsmentioning
confidence: 97%
See 2 more Smart Citations
“…The prevalence of SCC is higher in Pakistan and other South East Asian nations. 3 Risk of this cancer is intensified by direct and prolonged exposure to sunlight. 4 Patients presenting with squamous cell carcinoma unveil discrepancies in their signs and symptoms and response to treatment.…”
mentioning
confidence: 99%